A method for preparing a nanosilicon material
Patent Information
- Application Number
- CN202610131429.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2026-01-30
- Publication Date
- 2026-10-13
- Estimated Expiration
- 2046-01-30
AI Technical Summary
该氧化层不仅降低硅的电子导电性与离子扩散速率,还在电化学循环过程中参与副反应,导致首次库伦效率显著下降
[0024]本发明先对原料硅粉进行酸浸处理,然后将处理后的硅粉与油酸、没食子酸加入异丙醇中,经过一次球磨得到特定粒径范围的微纳米级硅粉浆料,再补加油酸和没食子酸,先经过高压均质处理,再进行二次球磨,得到纳米硅材料。本发明的制备方法工艺简单,生产效率高,得到的纳米硅材料不仅具有较小的粒径,而且氧含量低,不易被氧化,稳定性好,适合应用于锂离子电池负极材料领域。
Smart Images

Figure SMS_1 
Figure SMS_2 
Figure SMS_3
Abstract
Description
Technical Field
[0001] This invention relates to the field of silicon material preparation technology, and in particular to a method for preparing nano-silicon materials. Background Technology
[0002] Silicon (Si) has a theoretical specific capacity as high as 4200 mAh·g. -1 Silicon is considered one of the most promising anode materials for lithium-ion batteries. During the charge-discharge reaction, a reversible alloying reaction occurs between silicon and lithium. This process is accompanied by volume expansion and contraction of up to approximately 300%. These volume changes easily lead to problems such as particle pulverization, structural cracking, and electrode interface delamination. This results in repeated rupture and reconstruction of the solid electrolyte interphase (SEI) film, causing continuous consumption of active lithium, electrochemical contact failure, and rapid decay of reversible capacity, severely restricting its cycle stability and practical application performance. By using silicon nanostructure design, the absolute volume strain can be reduced, thereby improving the cycle stability of silicon anodes to some extent.
[0003] Currently, the mainstream method for preparing nano-silicon materials is grinding. During grinding, as well as during the storage and post-processing of the prepared nano-silicon materials, silicon readily undergoes spontaneous oxidation upon contact with air or oxygen-containing solutions, forming a surface oxide layer. This oxide layer not only reduces the electronic conductivity and ion diffusion rate of silicon but also participates in side reactions during electrochemical cycling, leading to a significant decrease in the initial coulombic efficiency. Furthermore, the surface oxide weakens the binding effect of carbon coating or interface modification, further exacerbating the volume effect and electrochemical instability. Therefore, effectively suppressing oxidation reactions and controllably removing the surface oxide layer during the preparation, storage, and post-processing stages of nano-silicon materials are crucial for maintaining the chemical activity of nano-silicon materials and improving the electrochemical performance of batteries made from them. Summary of the Invention
[0004] Based on the technical problems existing in the background technology, the present invention proposes a method for preparing nano-silicon materials.
[0005] The present invention proposes a method for preparing nano-silicon materials, comprising the following steps:
[0006] S1. Add industrial silicon powder to a mixed solution of hydrofluoric acid and hydrochloric acid, stir at room temperature for 3-5 hours, then filter, wash the obtained solid with isopropanol until pH≥6, and vacuum dry to obtain pretreated silicon powder.
[0007] S2. The pretreated silica powder, oleic acid, and gallic acid are added to isopropanol and ball-milled once until the particle size D50 is 0.8~1.1μm to obtain a ball-milled slurry; the mass ratio of the pretreated silica powder, oleic acid, gallic acid and isopropanol is 100:1~2:0.3~1:200~400.
[0008] S3. Add oleic acid and gallic acid to the primary ball milling slurry and perform high-pressure homogenization; the mass ratio of the primary ball milling slurry, oleic acid and gallic acid is 100:0.5~1.5:0.1~0.3.
[0009] S4. The material after high-pressure homogenization in S3 is ball-milled a second time until the particle size D50≤100nm, and the desired particle size is obtained.
[0010] The present invention first performs acid leaching treatment on the raw silicon powder; then the treated silicon powder, oleic acid, and gallic acid are added to isopropanol, and after one ball milling, a micro-nano silicon powder slurry with a specific particle size range is obtained. Then, oleic acid and gallic acid are added, and after high-pressure homogenization treatment, a second ball milling is performed to obtain nano-silicon material. The purpose of acid leaching is to remove oxides from the raw silicon powder and reduce its oxygen content. Oleic acid and gallic acid are used as dispersants and antioxidants, and isopropanol is used as a solvent. The silicon powder is first ball-milled to a specific particle size range. At this point, the particle size of the silicon powder reaches the micro-nano scale, and the specific surface area increases significantly, making it prone to agglomeration. Then, a certain amount of oleic acid and gallic acid are added, and high-pressure homogenization is performed. The shear force, impact, and cavitation effect of high-pressure homogenization, as well as the synergistic effect of the dispersant, allow the oleic acid and gallic acid to be fully adsorbed and spread on the surface of the micro-nano silicon powder, effectively improving the dispersibility and anti-oxidation properties of the micro-nano silicon powder. After a second ball milling, nano-sized silicon materials can be obtained efficiently, while also achieving a good anti-oxidation effect. This not only achieves the purpose of anti-oxidation during the preparation process and results in low oxygen content in the prepared silicon material, but the protective layer formed by oleic acid and gallic acid also makes the silicon material less susceptible to oxidation during storage and post-processing, thereby improving the electrochemical performance of the silicon material as a silicon anode material.
[0011] In summary, the preparation method of the present invention is simple and efficient, and the obtained nano-silicon material not only has a small particle size, but also low oxygen content, is not easily oxidized, and has good stability, making it suitable for application in the field of lithium-ion battery anode materials.
[0012] Preferably, the industrial silicon powder has a particle size of 200-500 mesh and a purity of >99%.
[0013] Preferably, in the mixed solution of hydrofluoric acid and hydrochloric acid, the concentration of hydrofluoric acid is 0.5~2 mol / L and the concentration of hydrochloric acid is 2~3 mol / L. The solvent for the mixed solution of hydrofluoric acid and hydrochloric acid is preferably water.
[0014] Preferably, in S1, the vacuum drying temperature is 50~70℃.
[0015] Preferably, in S2, the rotation speed of the ball mill is 100~200 r / min, and the time is 3~5 h.
[0016] Preferably, in S2, the first ball milling uses zirconia grinding balls with a diameter of 5-8 mm.
[0017] Preferably, in S3, the pressure of the high-pressure homogenization process is 30~50MPa, and the number of times is 2~3.
[0018] Preferably, in S4, the rotation speed of the secondary ball mill is 200~500 r / min, and the time is 8~12 h.
[0019] Preferably, in S4, the secondary ball milling uses zirconia grinding balls with a diameter of 0.1~0.5mm.
[0020] Preferably, in S2, the ball-to-material ratio of the first ball milling is 20~30:1.
[0021] Preferably, in S4, the ball-to-material ratio of the secondary ball mill is 20~30:1.
[0022] In step S4, after ball milling, conventional post-processing steps may be included, such as centrifugation, washing the obtained solid with isopropanol, and vacuum drying to obtain nano-silicon materials; preferably, the vacuum drying temperature is 50~70℃.
[0023] The beneficial effects of this invention are as follows:
[0024] This invention first performs acid leaching on raw silicon powder, then adds the treated silicon powder, oleic acid, and gallic acid to isopropanol. After a single ball milling process, a micro / nano-sized silicon powder slurry with a specific particle size range is obtained. Then, oleic acid and gallic acid are added, followed by high-pressure homogenization and a second ball milling process to obtain nano-silicon materials. The preparation method of this invention is simple, has high production efficiency, and produces nano-silicon materials with not only small particle size but also low oxygen content, making them resistant to oxidation and exhibiting good stability, suitable for application in the field of lithium-ion battery anode materials. Detailed Implementation
[0025] The technical solution of the present invention will now be described in detail through specific embodiments.
[0026] Example 1
[0027] A method for preparing nano-silicon materials, comprising the following steps:
[0028] S1. Industrial silicon powder with a particle size of 500 mesh and a purity >99% (oxygen content of 10300ppm) is added to a mixed solution of hydrofluoric acid and hydrochloric acid, stirred at room temperature for 5 hours, then filtered. The obtained solid is washed with isopropanol until pH≥6, and then vacuum dried at 60℃ to obtain pretreated silicon powder. The mixed solution of hydrofluoric acid and hydrochloric acid has the following composition: hydrofluoric acid 1mol / L, hydrochloric acid 2mol / L, and the balance is water.
[0029] S2. Pretreated silica powder, oleic acid, and gallic acid are added to isopropanol and ball-milled once at 150 r / min for 4 h to obtain a primary ball-milled slurry with a particle size D50 of 1.02 μm. The grinding balls used in the primary ball mill are zirconia grinding balls with a diameter of 5 mm and a ball-to-material ratio of 25:1. The mass ratio of pretreated silica powder, oleic acid, gallic acid, and isopropanol is 100:1:1:300.
[0030] S3. Add oleic acid and gallic acid to the primary ball milling slurry and homogenize it twice under high pressure at 40 MPa; wherein the mass ratio of the primary ball milling slurry, oleic acid and gallic acid is 100:1:0.2.
[0031] S4. The material after high-pressure homogenization in S3 is subjected to secondary ball milling at 400 r / min for 10 h, with a particle size D50 of 76 nm. The grinding balls used in the secondary ball milling are zirconia grinding balls with a diameter of 0.1 mm, and the ball-to-material ratio is 25:1. The slurry after secondary ball milling is centrifuged, and the resulting solid is washed with isopropanol and vacuum dried at 60 °C to obtain nano-silicon material.
[0032] Example 2
[0033] A method for preparing nano-silicon materials, comprising the following steps:
[0034] S1. Industrial silicon powder with a particle size of 500 mesh and a purity >99% (oxygen content of 10300ppm) is added to a mixed solution of hydrofluoric acid and hydrochloric acid, stirred at room temperature for 4 hours, then filtered. The obtained solid is washed with isopropanol until pH≥6, and then vacuum dried at 60℃ to obtain pretreated silicon powder. The mixed solution of hydrofluoric acid and hydrochloric acid has the following composition: hydrofluoric acid 1mol / L, hydrochloric acid 2mol / L, and the balance is water.
[0035] S2. Pretreated silica powder, oleic acid, and gallic acid are added to isopropanol and ball-milled once at 200 r / min for 5 h to obtain a primary ball-milled slurry with a particle size D50 of 0.88 μm. The grinding balls used in the primary ball mill are zirconia grinding balls with a diameter of 8 mm and a ball-to-material ratio of 30:1. The mass ratio of pretreated silica powder, oleic acid, gallic acid, and isopropanol is 100:2:0.5:400.
[0036] S3. Add oleic acid and gallic acid to the primary ball milling slurry, and perform high-pressure homogenization three times under a pressure of 30 MPa; wherein the mass ratio of the primary ball milling slurry, oleic acid and gallic acid is 100:0.5:0.1.
[0037] S4. The material after high-pressure homogenization in S3 is subjected to secondary ball milling at 300 r / min for 12 h, with a particle size D50 of 85 nm. The grinding balls used in the secondary ball milling are zirconia grinding balls with a diameter of 0.3 mm, and the ball-to-material ratio in the secondary ball milling is 30:1. The slurry after secondary ball milling is centrifuged, and the resulting solid is washed with isopropanol and vacuum dried at 60 °C to obtain nano-silicon material.
[0038] Example 3
[0039] A method for preparing nano-silicon materials, comprising the following steps:
[0040] S1. Industrial silicon powder with a particle size of 200 mesh and a purity >99% (oxygen content of 11600ppm) is added to a mixed solution of hydrofluoric acid and hydrochloric acid, stirred at room temperature for 3 hours, then filtered. The obtained solid is washed with isopropanol until pH≥6, and then vacuum dried at 60℃ to obtain pretreated silicon powder. The mixed solution of hydrofluoric acid and hydrochloric acid has the following composition: hydrofluoric acid 1mol / L, hydrochloric acid 2mol / L, and the balance is water.
[0041] S2. Pretreated silica powder, oleic acid, and gallic acid are added to isopropanol and ball-milled once at 200 r / min for 5 h to obtain a primary ball-milled slurry with a particle size D50 of 1.07 μm. The grinding balls used in the primary ball mill are zirconia grinding balls with a diameter of 5 mm and a ball-to-material ratio of 20:1. The mass ratio of pretreated silica powder, oleic acid, gallic acid, and isopropanol is 100:2:1:200.
[0042] S3. Add oleic acid and gallic acid to the primary ball milling slurry, and perform high-pressure homogenization twice under a pressure of 50 MPa; wherein the mass ratio of the primary ball milling slurry, oleic acid and gallic acid is 100:0.5:0.1.
[0043] S4. The material after high-pressure homogenization in S3 is subjected to secondary ball milling at 500 r / min for 8 h, with a particle size D50 of 97 nm. The grinding balls used in the secondary ball milling are zirconia grinding balls with a diameter of 0.5 mm, and the ball-to-material ratio is 20:1. The slurry after secondary ball milling is centrifuged, and the resulting solid is washed with isopropanol and vacuum dried at 60 °C to obtain nano-silicon material.
[0044] Comparative Example 1
[0045] A method for preparing nano-silicon materials, comprising the following steps:
[0046] S1. Industrial silicon powder with a particle size of 500 mesh and a purity >99% (oxygen content of 10300ppm) is added to a mixed solution of hydrofluoric acid and hydrochloric acid, stirred at room temperature for 5 hours, then filtered. The obtained solid is washed with isopropanol until pH≥6, and then vacuum dried at 60℃ to obtain pretreated silicon powder. The mixed solution of hydrofluoric acid and hydrochloric acid has the following composition: hydrofluoric acid 1mol / L, hydrochloric acid 2mol / L, and the balance is water.
[0047] S2. Add pretreated silica powder and oleic acid to isopropanol and ball mill for 4 hours at 150 r / min to obtain a primary ball mill slurry with a particle size D50 of 0.99 μm. The grinding balls used in the primary ball mill are zirconia grinding balls with a diameter of 5 mm and a ball-to-material ratio of 25:1. The mass ratio of pretreated silica powder, oleic acid and isopropanol is 100:2:300.
[0048] S3. Add oleic acid to the primary ball milling slurry and homogenize it twice under high pressure at 40 MPa; wherein the mass ratio of the primary ball milling slurry to oleic acid is 100:1.2.
[0049] S4. The material after high-pressure homogenization in S3 is subjected to secondary ball milling at 400 r / min for 10 h, with a particle size D50 of 73 nm. The grinding balls used in the secondary ball milling are zirconia grinding balls with a diameter of 0.1 mm, and the ball-to-material ratio is 25:1. The slurry after secondary ball milling is centrifuged, and the resulting solid is washed with isopropanol and vacuum dried at 60 °C to obtain nano-silicon material.
[0050] Comparative Example 2
[0051] A method for preparing nano-silicon materials, comprising the following steps:
[0052] S1. Industrial silicon powder with a particle size of 500 mesh and a purity >99% (oxygen content of 10300ppm) is added to a mixed solution of hydrofluoric acid and hydrochloric acid, stirred at room temperature for 5 hours, then filtered. The obtained solid is washed with isopropanol until pH≥6, and then vacuum dried at 60℃ to obtain pretreated silicon powder. The mixed solution of hydrofluoric acid and hydrochloric acid has the following composition: hydrofluoric acid 1mol / L, hydrochloric acid 2mol / L, and the balance is water.
[0053] S2. Add pretreated silica powder and gallic acid to isopropanol and ball mill at 150 r / min for 4 h to obtain a primary ball mill slurry with a particle size D50 of 2.95 μm. The grinding balls used in the primary ball mill are zirconia grinding balls with a diameter of 5 mm and a ball-to-material ratio of 25:1. The mass ratio of pretreated silica powder, gallic acid and isopropanol is 100:2:300.
[0054] S3. Add gallic acid to the primary ball milling slurry and homogenize it twice under high pressure at 40 MPa; wherein the mass ratio of the primary ball milling slurry to gallic acid is 100:1.2.
[0055] S4. The material after high-pressure homogenization in S3 is subjected to secondary ball milling at 400 r / min for 10 h, with a particle size D50 of 208 nm. The grinding balls used in the secondary ball milling are zirconia grinding balls with a diameter of 0.1 mm, and the ball-to-material ratio is 25:1. The slurry after secondary ball milling is centrifuged, and the resulting solid is washed with isopropanol and vacuum dried at 60 °C to obtain nano-silicon material.
[0056] Comparative Example 3
[0057] A method for preparing nano-silicon materials, comprising the following steps:
[0058] S1. Industrial silicon powder with a particle size of 500 mesh and a purity >99% (oxygen content of 10300ppm) is added to a mixed solution of hydrofluoric acid and hydrochloric acid, stirred at room temperature for 5 hours, then filtered. The obtained solid is washed with isopropanol until pH≥6, and then vacuum dried at 60℃ to obtain pretreated silicon powder. The mixed solution of hydrofluoric acid and hydrochloric acid has the following composition: hydrofluoric acid 1mol / L, hydrochloric acid 2mol / L, and the balance is water.
[0059] S2. Pretreated silica powder, oleic acid, and gallic acid are added to isopropanol and ball-milled once at 150 r / min for 4 h to obtain a primary ball-milled slurry with a particle size D50 of 1.02 μm. The grinding balls used in the primary ball mill are zirconia grinding balls with a diameter of 5 mm and a ball-to-material ratio of 25:1. The mass ratio of pretreated silica powder, oleic acid, gallic acid, and isopropanol is 100:1:1:300.
[0060] S3. Oleic acid and gallic acid were added to the primary ball milling slurry, and the mixture was ball milled a second time at 400 r / min for 10 h, resulting in a particle size D50 of 90 nm. The grinding balls used in the second ball milling were zirconia grinding balls with a diameter of 0.1 mm, and the ball-to-material ratio was 25:1. The mass ratio of the primary ball milling slurry, oleic acid, and gallic acid was 100:1:0.2. The slurry after the second ball milling was centrifuged, and the resulting solid was washed with isopropanol and vacuum dried at 60 °C to obtain nano-silicon materials.
[0061] The oxygen content of the nano-silicon materials obtained in Examples 1-3 and Comparative Examples 1-3 was tested, and the results are shown in Table 1.
[0062] Table 1
[0063]
[0064] The nano-silicon materials obtained in Examples 1-3 and Comparative Examples 1-3 were vacuum-packed and stored for 60 days, and then the oxygen content was tested. The test results are shown in Table 2.
[0065] Table 2
[0066]
[0067] Battery assembly was performed on the unstored and stored nano-silicon materials of Examples 1 and 1-3, respectively, and electrochemical performance was tested. The specific assembly steps are as follows: The negative electrode material, conductive agent (single-walled carbon nanotubes), and binder (lithium polyacrylate, PAALi) were mixed evenly at a mass ratio of 96:0.2:3.8, and an appropriate amount of high-purity water was added to obtain the negative electrode slurry. The negative electrode slurry was coated on copper foil and dried at 110°C for 10 hours in a vacuum drying oven. After rolling and punching, the negative electrode sheet was obtained. A lithium sheet was used as the counter electrode, and lithium hexafluorophosphate electrolyte was used as the electrolyte. The batteries were assembled into coin cells in a glove box under an argon atmosphere. The lithium hexafluorophosphate electrolyte was composed of lithium hexafluorophosphate, organic solvent, and additive FEC (fluoroethylene carbonate), wherein the concentration of lithium hexafluorophosphate was 1 mol / L, the mass of FEC accounted for 5% of the total mass of the electrolyte, and the organic solvent was composed of EC (ethylene carbonate) and DEC (diethyl carbonate) in a volume ratio of 1:1. The test rate was 0.1C. The electrochemical performance test results are shown in Table 3:
[0068] Table 3
[0069]
[0070] As can be seen from the above data, the method of the present invention can not only obtain nano-silicon materials with small particle size and low oxygen content, but also effectively inhibit the oxidation of silicon materials during storage and post-processing, thereby maintaining the activity and good electrochemical performance of silicon materials. Comparative Example 1 did not add gallic acid in the preparation of nano-silicon materials, resulting in nano-silicon materials with poor antioxidant effects; Comparative Example 2 did not add oleic acid in the preparation of nano-silicon materials, resulting in poor ball milling dispersion, larger particle size of the obtained nano-silicon materials, and severe powder agglomeration during the preparation process, leading to unsatisfactory antioxidant protection effects; Comparative Example 3 did not undergo high-pressure homogenization treatment before secondary ball milling, so the dispersant and antioxidant could not be well adsorbed and spread on the surface of the micro-nano-scale silicon materials, failing to achieve good anti-agglomeration and antioxidant effects during secondary ball milling, and exhibiting poor long-term inhibition of nano-silicon material oxidation.
[0071] The above description is only a preferred embodiment of the present invention, but the scope of protection of the present invention is not limited thereto. Any equivalent substitutions or modifications made by those skilled in the art within the scope of the technology disclosed in the present invention, based on the technical solution and inventive concept of the present invention, should be covered within the scope of protection of the present invention.
Claims
1. A method for preparing nano-silicon materials, characterized in that, Includes the following steps: S1. Add industrial silicon powder to a mixed solution of hydrofluoric acid and hydrochloric acid, stir at room temperature for 3-5 hours, then filter, wash the obtained solid with isopropanol until pH≥6, and vacuum dry to obtain pretreated silicon powder. S2. The pretreated silica powder, oleic acid, and gallic acid are added to isopropanol and ball-milled once until the particle size D50 is 0.8~1.1μm to obtain a ball-milled slurry; the mass ratio of the pretreated silica powder, oleic acid, gallic acid and isopropanol is 100:1~2:0.3~1:200~400. S3. Add oleic acid and gallic acid to the primary ball milling slurry and perform high-pressure homogenization treatment; the mass ratio of the primary ball milling slurry, oleic acid and gallic acid is 100:0.5~1.5:0.1~0.3; the pressure of the high-pressure homogenization treatment is 30~50MPa, and the number of times is 2~3. S4. The material after high-pressure homogenization in S3 is ball-milled a second time until the particle size D50≤100nm, and the desired particle size is obtained.
2. The method for preparing nano-silicon materials according to claim 1, characterized in that, The industrial silicon powder has a particle size of 200-500 mesh and a purity of >99%.
3. The method for preparing nano-silicon materials according to claim 1, characterized in that, In the mixed solution of hydrofluoric acid and hydrochloric acid, the concentration of hydrofluoric acid is 0.5~2 mol / L and the concentration of hydrochloric acid is 2~3 mol / L.
4. The method for preparing nano-silicon materials according to claim 1, characterized in that, In S2, the rotation speed of the ball mill is 100~200 r / min, and the time is 3~5 h.
5. The method for preparing nano-silicon materials according to claim 1, characterized in that, In S2, the first ball milling uses zirconia grinding balls with a diameter of 5-8 mm.
6. The method for preparing nano-silicon materials according to claim 1, characterized in that, In S4, the rotation speed of the secondary ball mill is 200~500 r / min, and the time is 8~12 h.
7. The method for preparing nano-silicon materials according to claim 1, characterized in that, In S4, the secondary ball milling uses zirconia grinding balls with a diameter of 0.1~0.5mm.
Citation Information
Patent Citations
Method and device for massively producing graphene conductive slurry and prepared graphene conductive slurry
CN108630338A
Method for preparing silicon-carbon negative electrode material from photovoltaic waste silicon powder and graphene oxide
CN114975962A
Silicon-carbon negative electrode material, preparation method thereof and electrochemical device
CN119725510A